Modern Curriculum Vitae: Wordless Meaning Delivery by Using Symbols - Luh Eka Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study was aimed to identify the effectiveness of the Wordless Curriculum Vitae and the perceptions of users in a number of hotels located in Badung, Bali upon the Wordless Curriculum Vitae. The method used was qualitative approach and data were obtained through the distribution of online questionnaires, interviews and documentation studies. The results showed that 90% of Modern Curriculum Vitae’s Human Resource users were able to attract their interest in processing to the next level (interview session) and conveying the meaning of language through icons (symbols) substitution. The CV could convey meaning effectively without changing the meaning. In conclusion, this Wordless CV by the substitution of the icons (symbols) has successfully delivered same meaning compared to the conventional CV. Keywords: Modern Curriculum Vitae, Use of Icon/Symbols, Wordless CV